2014
DOI: 10.1177/1071100714551386
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Alcohol Injection for Morton’s Neuroma

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Musson et al describe alcohol ablation under ultrasound control with 66% efficiency (pain relief) in the 14th month of the observation period [33]. In a study by Pasquali et al, 74% of over 500 patients achieved satisfactory results within a oneyear follow-up period [25]. While the majority of these studies are characterized by a short follow-up period, Gurdezi et al followed up the study participants for five years and concluded that alcohol injections provided results comparable to surgical excision [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musson et al describe alcohol ablation under ultrasound control with 66% efficiency (pain relief) in the 14th month of the observation period [33]. In a study by Pasquali et al, 74% of over 500 patients achieved satisfactory results within a oneyear follow-up period [25]. While the majority of these studies are characterized by a short follow-up period, Gurdezi et al followed up the study participants for five years and concluded that alcohol injections provided results comparable to surgical excision [26].…”
Section: Discussionmentioning
confidence: 99%
“…Many new noninvasive and effective methods for treating Morton's neuroma, such as ultrasound alcohol injection [25,26] and ultrasound radiofrequency ablation [27], raise the question of the usefulness of and the indications for surgical excision of the intermetatarsal nerve. The objective of this study was to evaluate the long-term follow-up results of neurectomy through a dorsal approach and to identify prognostic factors that can affect the final outcome.…”
mentioning
confidence: 99%
“…Real‐time assessment is another advantage of sonography and enables treatment of Morton neuromas by nonoperative injection of local anesthetic agents, alcohol, and corticosteroids into the affected space . In many cases, these treatments are performed under ultrasound guidance, which improves accuracy of the diagnosis.…”
mentioning
confidence: 99%
“…Ultrasound guided injection of alcohol is frequently used in the treatment of neuroma (Pasquali et al . ), ligamentous structures to control pain (Dagenais et al . ) and intravascularly with the aim of sclerosing abnormal vascular structures (Lee et al .…”
mentioning
confidence: 99%
“…In human medicine, ethanol sclerotherapy has several therapeutic applications. Ultrasound guided injection of alcohol is frequently used in the treatment of neuroma (Pasquali et al 2015), ligamentous structures to control pain (Dagenais et al 2006) and intravascularly with the aim of sclerosing abnormal vascular structures (Lee et al 2003;Qiu et al 2013). Neurological structures can also be targeted as in the desensitisation of the coeliac ganglion to curtail emesis and pain caused by peritoneal inflammation and abdominal neoplasia (Collazos et al 1996).…”
mentioning
confidence: 99%